IMPLEMENTATION OF THE GENERALIZED AUTOREGRESSIVE CONDITIONAL HETEROSCEDASTICITY METHOD FOR FORECASTING THE STOCK RETURN OF PT LIPPO GENERAL INSURANCE TBK - Bariq, Muhammad Shidqi Abdul; Sartono, Bagus; Sofia, Ayu (Statistics Study Programme, Department of Mathematics, Faculty of Mathematics and Natural Sciences, University of Pattimura, 2025)
The Indonesian capital market is one of the investment destinations for investors from developed countries. The development of Indonesia's economic conditions is considered good for investors in investing their funds. Financial sector shares are one of the sectors that has experienced development throughout this year. One of the seven stocks showing good growth is PT Lippo General Insurance Tbk (LPGI). The important thing that is the main concern of investors is the level of yield or return from a stock. Based on this, stock return forecasting analysis can be important information for investors. This research uses the GARCH method to forecast LPGI stock returns. The analysis results show that the best model for LPGI stock returns is ARIMA (2,0,0) GARCH (1,1) with a very small return value and a negative sign. Thus, these results provide information that the forecasting period is not the right time for investors to buy LPGI shares. However, investors who have bought LPGI shares and made a profit are advised to sell LPGI shares before the forecast period. The empirical evidence from this study demonstrates that the GARCH model can effectively capture the volatility pattern of LPGI stock returns in n financial market. This finding supports the application of GARCH in modeling return fluctuations in emerging markets.